2022
DOI: 10.12669/pjms.38.6.5928
|View full text |Cite
|
Sign up to set email alerts
|

Acute and subacute toxicity studies of a poly herbal formulation used for diabetes

Abstract: Objectives: PHF-dia (Poly Herbal Formulation Diabetes) is a polyhedral formulation possessing antihyperglycemic and antihyperlipdimic effects. This study aims to assess acute and sub-acute toxicity of PHF-dia in rats. Methods: This is an experimental study conducted in two different phases. Acute toxicity was conducted for 14 days and sub-acute toxicity was conducted for 28 days. Both studies were conducted in animal house of Jinnah University for Women, Karachi, Pakistan. Acute toxicity was evaluated in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Clinical observations performed during the trial in animals assigned to the dosage and surveillance groups showed that oral administration of VNC during the sub-acute toxicity study period had no adverse effect on rat development and physiological functions. The current sub-acute toxicity investigation estimated biochemical and hematological assessments because they are among the essential indicators for gauging the safety of the formulation (Ghauri et al, 2022). There was no recovery in the surveillance group, and the male rats in the therapy group exhibited no signs of improvement in HGB, RBC count, PCV, PLT count, or MCH [Table 7)].…”
Section: Discussionmentioning
confidence: 99%
“…Clinical observations performed during the trial in animals assigned to the dosage and surveillance groups showed that oral administration of VNC during the sub-acute toxicity study period had no adverse effect on rat development and physiological functions. The current sub-acute toxicity investigation estimated biochemical and hematological assessments because they are among the essential indicators for gauging the safety of the formulation (Ghauri et al, 2022). There was no recovery in the surveillance group, and the male rats in the therapy group exhibited no signs of improvement in HGB, RBC count, PCV, PLT count, or MCH [Table 7)].…”
Section: Discussionmentioning
confidence: 99%